Comparative study of open onlay mesh repair versus laparoscopic intraperitoneal dual mesh repair for ventral hernia - Surya Prakash; Asha Gaud; Dinesh Kumar (Asian Journal of Medical Sciences, 2024)
Background: Ventral abdominal wall hernia surgery is a common procedure in the armamentarium of surgeons. The most common forms of these surgical procedures in adults are the repair of incisional hernias and surgery for paraumbilical hernias. Aims and Objectives: Open onlay mesh repair versus laparoscopic intraperitoneal dual mesh repair (intraperitoneal onlay mesh [IPOM]) for ventral hernia compared to the duration of surgery, post-operative pain, postoperative complications, post-operative hospital stay, return to normal activity, recurrence, and cosmesis. Materials and Methods: The prospective non-randomized study was done in the Maharani Laxmi Bai Medical College, Jhansi, between January 2021 and June 2022 including 100 patients was applied for treatment of ventral hernia repair. Fifty patients were subjected to Group A (open onlay mesh repair) and 50 patients were subjected to Group B (laparoscopic intraperitoneal dual mesh repair). Results: The mean surgery durations were significantly lower in laparoscopic repair when compared to open repair (P<0.001). The mean post-operative stay in the hospital was shorter for the laparoscopic group than for the open hernia group (10.28±2.100 vs. 8.02±1.378 days; P≤0.001). Return to activity or normal daily work is significantly lower in the laparoscopic group as compared to open repair of hernia (5.12±0.659 vs. 2.94±0.550 days; P<0.001). There were fewer post-operative complications with laparoscopy. Conclusion: Laparoscopic intraperitoneal dual mesh repair (IPOM) for ventral hernia in our experience was safe and resulted in fewer complications, shorter hospital stays, and better cosmesis results. Hence, it should be considered the better choice for ventral hernia repair.